Effect of Humic acid, Cytokinin and Arginine on Growth and Yield Traits of Bean Plant Phaseolus vulgaris L. under salt stress (Baghdad Science Journal, 2024)
To achieve optimal plant growth and production under salt stress, some products were added in adequate quantities to give a good yield, especially bean plants which are sensitive to salinity. For this purpose, this experiment was carried out during the spring growing season in 2022 in Baghdad, to study the effects of humic acid, cytokinin, arginine and their interaction with 9 parameters that reflect the overall traits of vegetative growth and yield of common bean plants Phaseolus vulgaris L. var. Astraid (from MONARCH seeds, China). The factorial design with 3 replicates was used, each with 7 plants treated via foliar spraying or by addition to the soil. The first factor included three groups; H0, H1 and H2 (0, 6, 12 Kg.h-1 Humic acid). The second factor included two groups; C0, and C1 [0, 100 mg.l-1 Cytokinins], and the third factor included three groups; A0, A1 and A2 (0, 100, 200 mg.l-1 Arginine). During the period of plant growing, furrow irrigation with drip pipe irrigation was used regularly with non-saline water EC= 2.2, during the first growth stage until it reaches the stage of four true leaves then irrigated with well saline water EC=3.4 for the rest of the plant life cycle. As for the treatment with humic acid, the results revealed that H2 treatment caused significantly higher values in most the studied traits. For cytokinin treatment, the results showed that C1 treatment resulted in significantly higher values in most the studied traits. And, there was no significant difference between A0, A1, and A2 except for leaves area, shoot dry weight, and root dry weight which exerts a significant difference between (A1, A2) in comparison to control A0. Based on the results of the binary overlap among treatments, H2C1, H2A2, H2A1 and, triple overlap H2C1A2 and H2C1A1 treatments resulted in the highest values as compared to all other treatments for all the studied traits. In conclusion, the present study comes up with the following: humic acid, cytokinin, arginine, and their interactions enhance most of the plant growth parameters and the pods production of common bean plants under salt stress.